Empathy, the Other and Engaged Acts - Igor Cvejić, Petar Bojanić (Bollettino Filosofico, 2022)
In this paper we consider the correlation and interdependence between empathy and engaged acts, i.e., acts undertaken in interacting with the other or others, through which the first-person singular shifts to the first-person plural. We argue that engaged acts are a constitutive element of empathy. To support our thesis, we address some issues with the common notion of empathy, specifically, those related to the first-person and third-person accounts. Further, we discuss their alternatives in phenomenology and interaction theories. In particular, we address two important aspects of empathy: that of the second person perspective, and the issue of the Self/Other differentiation. In the final part of the paper, we portray the phenomenological structure of engaged acts. Keywords: Empathy, Engaged Acts, Engagement, Second-Person Perspective, Self/Other Differentiation